Retention behavior of cesium radioisotope on poly (acrylamido-sulfonic acid) synthesized by chain polymerization. (April 2019) - Hassan, H.S.; Elmaghraby, Elsayed K.
Abstract: Poly (acrylamido-sulfonic acid) polymers have been synthesized using the technique of radical chain polymerization utilizing acrylamide and ammonium persulphate. The polymerization was triggered and controlled using radiation from 1.1 μ Ci radium source. The polymer sheet was characterized using FTIR, DTA, TG, XRD and SEM. The sorption behavior of the prepared polymer was investigated for 137 Cs radionuclide from acid medium (nitric acid). Different parameters such as shaking time and concentrations of HNO3 have been investigated. The removal of 137 Cs obeys the pseudo-second-order mechanism. The maximum monolayer capacity of polymer was 139.7 mg/g at room temperature. The thermodynamic parameters such as ΔG°, ΔH° and ΔS° were calculated. Highlights: Poly (acrylamido-sulfonic acid) polymers as sorbent materials was prepared by radical chain polymerization technique. The sorption behavior of the prepared polymer was investigated for 137 Cs radionuclide from acid medium. The estimated monolayer capacity was found 139.7 mg/g for 137 Cs.